The genus Massalongia (lichenised ascomycetae) in the Southern Hemisphere - Jørgensen, Per Magnus; Andersen, Heidi; Elvebakk, Arve (MycoKeys, 2019)
The species of Massalongia recorded and described from the Southern Hemisphere are revised and it is shown that only one is present; M. patagonica which is widespread, with populations in Australia and New Zealand that differ from the South American populations, but at present best regarded as part of the variation of that species. Records from this hemisphere of all other species placed in the genus are incorrect. The type species, M. carnosa , is restricted to the Northern Hemisphere. Two species, M. antarctica and M. novozelandica cannot be identified precisely due to lack of sufficient type material and with the types as the only collections known of these, but none belongs in Massalongia according to available data. Massalongia griseolobata (from Gough Isl.) is shown here to belong in the Pannariaceae and is part of the parmelielloid clade. M. intricata (from South Georgia) and M. olechiana (from South Shetland) have both recently been correctly transferred to the genus Steinera in the Arctomiaceae.